Longitudinal double-spin asymmetry for inclusive jet and dijet production in polarized proton collisions at √s=200 GeV - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2021)
STAR Collaboration: M.S. Abdallah, J. Adam, L. Adamczyk, J.R. Adams, J.K. Adkins, G. Agakishiev, I. Aggarwal, M.M. Aggarwal, Z. Ahammed, I. Alekseev, D.M. Anderson, A. Aparin, E.C. Aschenauer, M.U. Ashraf, F.G. Atetalla, A. Attri, G.S. Averichev, V. Bairathi, W. Baker, J.G. Ball Cap, K. Barish, A. Behera, R. Bellwied, P. Bhagat, A. Bhasin, J. Bielcik, J. Bielcikova, I.G. Bordyuzhin, J.D. Brandenburg, A.V. Brandin, I. Bunzarov, J. Butterworth, X. Z. Cai, H. Caines, M. Calderón de la Barca Sánchez, D. Cebra, I. Chakaberia, P. Chaloupka, B. K. Chan, F-H. Chang, Z. Chang, N. Chankova-Bunzarova, A. Chatterjee, S. Chattopadhyay, D. Chen, J. Chen, J.H. Chen, X. Chen, Z. Chen, J. Cheng, M. Chevalier, S. Choudhury, W. Christie, X. Chu, H.J. Crawford, M. Csanád, M. Daugherity, T.G. Dedovich, I.M. Deppner, A.A. Derevschikov, A. Dhamija, L. Di Carlo, L. Didenko, X. Dong, J.L. Drachenberg, J.C. Dunlop, N. Elsey, J. Engelage, G. Eppley, S. Esumi, O. Evdokimov, A. Ewigleben, O. Eyser, R. Fatemi, F.M. Fawzi, S. Fazio, P. Federic, J. Fedorisin, C.J. Feng, Y. Feng, P. Filip, E. Finch, Y. Fisyak, A. Francisco, C. Fu, L. Fulek, C.A. Gagliardi, T. Galatyuk, F. Geurts, N. Ghimire, A. Gibson, K. Gopal, X. Gou, D. Grosnick, A. Gupta, W. Guryn, A.I. Hamad, A. Hamed, Y. Han, S. Harabasz, M.D. Harasty, J.W. Harris, H. Harrison, S. He, W. He, X. H. He, Y. He, S. Heppelmann, S. Heppelmann, N. Herrmann, E. Hoffman, L. Holub, Y. Hu, H. Huang, H.Z. Huang, S.L. Huang, T. Huang, X. Huang, Y. Huang, T.J. Humanic, D. Isenhower, W.W. Jacobs, C. Jena, A. Jentsch, Y. Ji, J. Jia, K. Jiang, X. Ju, E.G. Judd, S. Kabana, M.L. Kabir, S. Kagamaster, D. Kalinkin, K. Kang, D. Kapukchyan, K. Kauder, H.W. Ke, D. Keane, A. Kechechyan, Y.V. Khyzhniak, D.P. Kikoła, C. Kim, B. Kimelman, D. Kincses, I. Kisel, A. Kiselev, A.G. Knospe, L. Kochenda, L.K. Kosarzewski, L. Kramarik, P. Kravtsov, L. Kumar, S. Kumar, R. Kunnawalkam Elayavalli, J.H. Kwasizur, R. Lacey, S. Lan, J.M. Landgraf, J. Lauret, A. Lebedev, R. Lednicky, J. H. Lee, Y.H. Leung, C. Li, C. Li, W. Li, X. Li, Y. Li, X. Liang, Y. Liang, R. Licenik, T. Lin, Y. Lin, M.A. Lisa, F. Liu, H. Liu, P. Liu, T. Liu, X. Liu, Y. Liu, Z. Liu, T. Ljubicic, W.J. Llope, R.S. Longacre, E. Loyd, N.S. Lukow, X. Luo, L. Ma, R. Ma, Y.G. Ma, N. Magdy, R. Majka, D. Mallick, S. Margetis, C. Markert, H.S. Matis, J.A. Mazer, N.G. Minaev, S. Mioduszewski, B. Mohanty, M.M. Mondal, I. Mooney, D.A. Morozov, A. Mukherjee, M. Nagy, J.D. Nam, Md. Nasim, K. Nayak, D. Neff, J.M. Nelson, D.B. Nemes, M. Nie, G. Nigmatkulov, T. Niida, R. Nishitani, L.V. Nogach, T. Nonaka, A.S. Nunes, G. Odyniec, A. Ogawa, S. Oh, V.A. Okorokov, B.S. Page, R. Pak, A. Pandav, A.K. Pandey, Y. Panebratsev, P. Parfenov, B. Pawlik, D. Pawlowska, H. Pei, C. Perkins, L. Pinsky, R.L. Pintér, J. Pluta, B.R. Pokhrel, G. Ponimatkin, J. Porter, M. Posik, V. Prozorova, N.K. Pruthi, M. Przybycien, J. Putschke, H. Qiu, A. Quintero, C. Racz, S.K. Radhakrishnan, N. Raha, R.L. Ray, R. Reed, H.G. Ritter, M. Robotkova, O.V. Rogachevskiy, J.L. Romero, L. Ruan, J. Rusnak, N.R. Sahoo, H. Sako, S. Salur, J. Sandweiss, S. Sato, W.B. Schmidke, N. Schmitz, B.R. Schweid, F. Seck, J. Seger, M. Sergeeva, R. Seto, P. Seyboth, N. Shah, E. Shahaliev, P.V. Shanmuganathan, M. Shao, T. Shao, A.I. Sheikh, D. Shen, S. S. Shi, Y. Shi, Q.Y. Shou, E.P. Sichtermann, R. Sikora, M. Simko, J. Singh, S. Singha, M.J. Skoby, N. Smirnov, Y. Söhngen, W. Solyst, P. Sorensen, H.M. Spinka, B. Srivastava, T.D.S. Stanislaus, M. Stefaniak, D.J. Stewart, M. Strikhanov, B. Stringfellow, A.A.P. Suaide, M. Sumbera, B. Summa, X. M. Sun, X. Sun, Y. Sun, Y. Sun, B. Surrow, D.N. Svirida, Z.W. Sweger, P. Szymanski, A.H. Tang, Z. Tang, A. Taranenko, T. Tarnowsky, J.H. Thomas, A.R. Timmins, D. Tlusty, T. Todoroki, M. Tokarev, C.A. Tomkiel, S. Trentalange, R.E. Tribble, P. Tribedy, S.K. Tripathy, T. Truhlar, B.A. Trzeciak, O.D. Tsai, Z. Tu, T. Ullrich, D.G. Underwood, I. Upsal, G. Van Buren, J. Vanek, A.N. Vasiliev, I. Vassiliev, V. Verkest, F. Videbæk, S. Vokal, S.A. Voloshin, F. Wang, G. Wang, J.S. Wang, P. Wang, Y. Wang, Y. Wang, Z. Wang, J.C. Webb, P.C. Weidenkaff, L. Wen, G.D. Westfall, H. Wieman, S.W. Wissink, R. Witt, J. Wu, Y. Wu, B. Xi, Z.G. Xiao, G. Xie, W. Xie, H. Xu, N. Xu, Q. H. Xu, Y. Xu, Z. Xu, Z. Xu, C. Yang, Q. Yang, S. Yang, Y. Yang, Z. Ye, Z. Ye, L. Yi, K. Yip, Y. Yu, H. Zbroszczyk, W. Zha, C. Zhang, D. Zhang, S. Zhang, S. Zhang, X.P. Zhang, Y. Zhang, Y. Zhang, Y. Zhang, Z.J. Zhang, Z. Zhang, Z. Zhang, J. Zhao, C. Zhou, X. Zhu, Z. Zhu, M. Zurek, M. Zyzak
Gesehen am 15.09.2022